Characterization of an RNA binding protein interactome reveals a context-specific post-transcriptional landscape of MYC-amplified medulloblastoma - Kameda-Smith, Michelle M; Zhu, Helen; Luo, En-Ching; Suk, Yujin; Xella, Agata; Yee, Brian; Chokshi, Chirayu; Xing, Sansi; Tan, Frederick; Fox, Raymond G; Adile, Ashley A; Bakhshinyan, David; et al. (Nature communications, 2022)
Pediatric medulloblastoma (MB) is the most common solid malignant brain neoplasm, with Group 3 (G3) MB representing the most aggressive subgroup. MYC amplification is an independent poor prognostic factor in G3 MB, however, therapeutic targeting of the MYC pathway remains limited and alternative therapies for G3 MB are urgently needed. Here we show that the RNA-binding protein, Musashi-1 (MSI1) is an essential mediator of G3 MB in both MYC-overexpressing mouse models and patient-derived xenografts. MSI1 inhibition abrogates tumor initiation and significantly prolongs survival in both models. We identify binding targets of MSI1 in normal neural and G3 MB stem cells and then cross referenced these data with unbiased large-scale screens at the transcriptomic, translatomic and proteomic levels to systematically dissect its functional role. Comparative integrative multi-omic analyses of these large datasets reveal cancer-selective MSI1-bound targets sharing multiple MYC associated pathways, providing a valuable resource for context-specific therapeutic targeting of G3 MB.
Keywords: Mice; Nerve Tissue Proteins; meduloblastom; proteiny vázající RNA; nádory mozku; Medulloblastoma; proteiny nervové tkáně; Animals; Cerebellar Neoplasms; Humans; RNA-Binding Proteins; lidé; zvířata; Brain Neoplasms; myši; Proteomics; proteomika; nádory mozečku